Far-field scattering regulation of all dielectric material metagratings based on the addition principle of coding elements. Issue 17 (22nd November 2022) - Wei, Hongling; Cui, Fuyi; Guo, Weigang; Wu, Yinglai; Lu, Jianxun; Huang, Wenkang; Xu, Libo; Li, Ruisi; Li, Chenxia; Jing, Xufeng
Abstract : The coding metasurface is a way of digital coding to simplify the design of the unit, which can control electromagnetic waves more simply and efficiently. To reduce ohmic losses and improve the efficiency of encoded metasurface devices, we propose all-dielectric encoded unit structure with silicon material. Based on the parameter scanning optimization method, we designed 1-bit coding unit, 2-bit coding unit and 3-bit coding unit. By rationally arranging these coding units, we construct coding metasurfaces with different sequences. In order to realize multi-angle and multi-function scattering control, we introduce the addition principle of digital codes. Two basic encoding sequences can be added to obtain a new added encoding sequence. The multi-angle and multi-function far-field control through digital code addition operation of two basic sequences of encoding metagratings can be obtained.